Undoing performance in micro finance institutions: Reflections on regulatory framework in Kenya - Victor Mwendwa Muithya; Stephen Muathe; Godfrey Kinyua (The Journal of Entrepreneurial Finance (JEF), 2022)
The performance of Micro Finance Institutions (MFIs) has been affected negatively by the current hypercompetitive economic environment which has beencharacterised by as unfair competition. Huge losses have been reported among MFIs in Kenya, this has forced MFIs to innovate differently; product, financial, organisational or market innovation. This has not yielded better results. The study sought to establish the moderating effect of the regulatory framework on the relationship between strategic innovation orientation and performance of MFIs using the case of Kenya. The indicators for the regulatory framework were; prudential guidelines, non-prudential guidelines, and government laws. A descriptive and explanatory research design was adopted as the research design with a target population of 13 MFIs from which a sample of 352 respondents was obtained using a proportionate stratified and simple random sampling technique. Both financial and non-financial measures of performance were collected and analysed using mutiple regression. The regulatory framework was found to have a moderating effect on the relationship between strategic innovation orientation and performance. The findings established that regulatory framework had a moderating effect on the relationship between strategic innovation orientation and performance of MFIs. This informs the importance of regulation and control by regulatory bodies and the government.
Keywords: 650; Strategic innovation orientation; regulatory framework; Micro Finance Institutions and Performance